Direct-DC Power System Generation Based on Single-Phase Rooftop Photovoltaic in Residential Low Voltage Feeder - Siti Amra; Nelly Safitri; Akhyar Akhyar; Usmardi Usmardi (Journal of Multidisciplinary Academic, 2017)
The trend of converting direct current (DC) system into alternating current (AC) using inverter becomes common since the system efficiency appropriately improves. Additionally, the mitigation on direct-DC power system requires transformer and inverters inside the appliances due to lower and convert the 230VAC into useable DC voltage. This paper proposes the direct-DC power system generation based on single-phase rooftop photovoltaic (PV) in the residential low voltage (LV) feeder. The proposed simulation designates the power system components included in the modeling of the AC and direct-DC houses, which the included power system components downstream of the PV array. The efficiency of direct-DC power supply, grid interactive inverter and charge controller are simulated. The results show that the peak curve efficiency of direct-DC power supply has DC power input narrow to 400VDC. It is then become 2% higher than 220VAC power input. While the inverter with multiple MPPT efficiency curve has the peak of 96-97% after 30% loads, while when it is partly loads, with the power capacity below 1000W, has peak at range of 86-95%. Then the efficiency curve of charge controller with MPPT for partly load scheme below 30W output power the peak is about 90-94%.